Alcopops Disproportionately Consumed by Minors in Sexual Assault Cases - Matthew E. Rossheim; Kwynn M. Gonzalez-Pons; Kayla K. Tillett; Ryan D. Treffers; Pamela J. Trangenstein; Jennifer Lerch; Faye S. Taxman; Kaylin M. Greene; Cassidy R. LoParco; David H. Jernigan (New Prairie Press, 2023)
Alcohol is present in a large proportion of sexual assault cases. However, research largely overlooks the role that providing alcoholic beverages - particularly those with high-alcohol- content and/or whose flavors mask the taste of alcohol - may have in making young people more vulnerable to being assaulted. This research is especially important given the rise in the availability of sugar-sweetened alcopops and their high-alcohol-content counterparts "supersized alcopops," which contain up to 5.5 standard alcoholic drinks. In the current study, we examined whether alcopops and supersized alcopops, relative to beer, were involved in disproportionately more sexual assault cases involving victims who were minors (< 18 years old) rather than adults. In this secondary data analysis, we used Nexis Uni to search legal documents for the brands of supersized alcopop (Four Loko), alcopop (Smirnoff Ice), and beer (Bud Light) most commonly consumed by underage drinkers. Inclusion criteria were U.S. sexual assault cases occurring from 2010 to 2019 and involving victims who consumed one of these three alcohol brands. Two researchers coded information from the case facts, compared coding, and reaching consensus. Thirty-six cases were included for analyses. Compared to victims of sexual assault who consumed beer, victims who consumed supersized alcopops or alcopops were significantly more likely to be minors. Similar results were observed after adjusting for the victim being given the alcohol by the perpetrator, which was strongly associated with the victim being a minor. This study provides initial evidence that sexual assault perpetrators may disproportionately use alcopops and supersized alcopops for the sexual victimization of minors.